2017
DOI: 10.1097/ypg.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Definition of a putative pathological region in PARK2 associated with autism spectrum disorder through in silico analysis of its functional structure

Abstract: Although PARK2 may be a pathological factor for NDDs, likely not all variants are pathogenic, and a conclusive assessment of PARK2 variant pathogenicity requires an accurate analysis of their location within the coding region and encoded functional domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 64 publications
3
27
3
Order By: Relevance
“…It has been suggested that CNVs affecting exons 5–12 result in a more severe phenotype than those affecting exons 2–4. On the other hand, within exons 2–4, duplications lead to a more severe phenotype than deletions, due to greater interference to gene expression [11, 49]. Our findings in this cohort echo the above observations in that the largest duplication in PARK2 was indeed found in a patient with ASD, while the smaller deletions involving only exon 2 were identified in non-ASD patients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been suggested that CNVs affecting exons 5–12 result in a more severe phenotype than those affecting exons 2–4. On the other hand, within exons 2–4, duplications lead to a more severe phenotype than deletions, due to greater interference to gene expression [11, 49]. Our findings in this cohort echo the above observations in that the largest duplication in PARK2 was indeed found in a patient with ASD, while the smaller deletions involving only exon 2 were identified in non-ASD patients.…”
Section: Discussionsupporting
confidence: 84%
“…While the duplication of patient 6 involved exons 2–4, the other two deletions overlap exon 2 only. Both deletions and duplications involving PARK2 have been associated with ASD with variable expressivity and incomplete penetrance [11, 49]. When considering the pathogenicity, the size of the CNV, exons involved, and whether it was a copy gain or loss should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Since loss‐of‐function variants in PARK2 cause autosomal recessive Type 2 Juvenile Parkinson disease (OMIM #600116), and CNVs affecting PARK2 have been described in individuals with neurodevelopmental disorders (Mariani et al, ; Palumbo et al, ), we looked into the possibility that the PARK2 exon 2 duplication could be contributing to the behavioral problems in Patient 1. However, a recent study by Conceição et al suggests that primarily CNV's targeting the C‐terminal exons, corresponding to the ring‐between‐ring (RBR) domain, are responsible for the neurodevelopmental symptomology, as opposed to N‐terminal CNV's that are just as common in healthy controls (Conceição et al, ). Since the CNV of Patient 1 only involved exon 2 in the N‐terminal region of the gene, it seems less likely to be the sole cause of his behavioral problems.…”
Section: Discussionmentioning
confidence: 99%
“…Together, our studies implicate glutamatergic synaptic dysfunction in the etiology of motor and non-motor symptoms experienced by PARK2 patients. Intriguingly, recent genome-wide association studies report that PARK2 deletions and copy number variations (CNVs) are also associated with autism, schizophrenia, and intellectual disability (35,(66)(67)(68), disorders linked to dysfunction of excitatory glutamatergic signaling. These new findings further underscore the importance of elucidating Parkin's molecular mechanisms of action at glutamatergic synapses, both to facilitate the development of better treatments for motor and non-motor symptoms of PARK2-linked PD, and to shed light on its emerging role in the etiology of neuropsychiatric disease.…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 pathogenic mutations have been identified in PARK2, comprising point mutations, deletions, and exonic rearrangements that are associated with early-onset PD and autosomal recessive juvenile PD (5,35,36). However, few of these have been evaluated for their impact on excitatory synapse function.…”
Section: Pathogenic Parkin Mutations Alter Ampar and Nmdar Cell-surfamentioning
confidence: 99%